Penetration depth study of LaOs4Sb12 : multiband s-wave superconductivity - Panagopoulos, Christos (2013)
We measured the magnetic penetration depth λ(T) in single crystals of LaOs4Sb12 (Tc=0.74 K) down to 85 mK using a tunnel-diode-oscillator technique. The observed low-temperature exponential dependence indicates an s-wave gap. Fitting the low-temperature data to a BCS s-wave expression gives the zero-temperature gap value Δ(0)=(1.34±0.07)kBTc which is significantly smaller than the BCS value of 1.76kBTc. In addition, the normalized superfluid density ρ(T) shows an unusually long suppression near Tc and is best fit by a two-band s-wave model.